LINGKUNGAN PENDIDIKAN DALAM AL-QUR’AN DAN HADIS - Hasbullah, Hasbullah (Tarbawi, 2018)
Educational environment is needed in the education process, because the educational environment serves to support the process of teaching and learning, a comfortable environment and support for the implementation of an education is needed. The environment is distinguished into the biological environment, the non-living natural environment, the artificial environment and the social environment. Education is one of the first obligations for parents. In Islam, the person most responsible for the education of the child is the parent. The family is the "smallest people" who have leaders and members, has a division of work and work, and the rights and obligations of each member. The best exemplary education for children is if both parents are able to connect their child with the example of Rasûlullâh SAW, as uswah of all mankind. A positive school environment is a school environment that provides facilities and motivation for religious education. Keywords. Environment, Education